Elaboración y comercialización de cerveza artesanal “FLUMINENSE” - Preciado Vásquez, María Fernanda (2019)
The purpose of this research is to carry out an entrepreneurial project for the elaboration and analysis of a product called Fluminense craft beer in presentation of 330 ml, with its latest brand name. The same one that will be located in the city of Babahoyo, province of Los Ríos. The implementation of this Fluminense beer enterprise modifying the use of different research methods; inductive, deductive, analytical, statistical. A market study was considered that through a survey of 382 inhabitants of the city of Babahoyo, in order to determine if there is an unsatisfied demand that could benefit and offer the product. The product to offer will be destined to the market segment of men and women over 18 years of age, the venture will start with blonde beer Pale Ale. The initial investment of the project is $ 10,000 which will be financed by the public bank BanEcuador. When carrying out the financial feasibility, the net present value is: 47,587.14 which indicates that the project is viable, the internal rate of return TIR is 124% satisfactory to carry out the project, the payment is the number of years and months that It takes the project to recover the initial investment therefore the project recovers in 10 months and 20 days, this implies that it is acceptable, since the bank loan is a 3-year term, as well as the cost benefit ratio showed us that for every dollar Invested you get a return of $ 1.51 for each product sold